2020
DOI: 10.1007/s00264-020-04768-7
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient surgery in patients with ankle fractures minimises hospital admissions and utilisation of healthcare resources

Abstract: Purpose The recent outbreak of the novel coronavirus (SARS-CoV-2) has emphasised the need to minimise hospital admissions and utilisation of healthcare resources. The purpose of this study was to examine the outcomes of an outpatient surgery protocol for acute closed ankle fractures. Methods In this retrospective study, 262 patients underwent outpatient surgery for their closed ankle fractures at our level-1 trauma centre. A total of 196 patients met our inclusion criteria and were ultimately included in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Since the evolution of the pandemic, reduced number of clinical cases have been observed in the orthopaedic outpatient departments (OPDs) along with the cancellations of elective surgeries resulting in lesser orthopaedic patient admission to hospitals [ 1 , 4 ]. Moreover, the task forces employed to manage the pandemic in various countries called for a delay or cancellation of all non-essential or elective surgeries.…”
Section: Impact Of Covid-19 On Orthopaedic Departments Organizations ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the evolution of the pandemic, reduced number of clinical cases have been observed in the orthopaedic outpatient departments (OPDs) along with the cancellations of elective surgeries resulting in lesser orthopaedic patient admission to hospitals [ 1 , 4 ]. Moreover, the task forces employed to manage the pandemic in various countries called for a delay or cancellation of all non-essential or elective surgeries.…”
Section: Impact Of Covid-19 On Orthopaedic Departments Organizations ...mentioning
confidence: 99%
“…Moreover, the task forces employed to manage the pandemic in various countries called for a delay or cancellation of all non-essential or elective surgeries. These decisions were taken to conserve healthcare resources (e.g., PPE, gloves, intensive care unit (ICU) beds, ventilators), reduce the risk of contagion transmission, reduce hospital admissions and enhance the capacity to support patients with COVID-19 [ 4 , 5 ]. Furthermore, one of the early studies conducted after the COVID-19 restrictions revealed a 32% reduction in trauma cases due to people remaining indoors during this period [ 6 ].…”
Section: Impact Of Covid-19 On Orthopaedic Departments Organizations ...mentioning
confidence: 99%
“…Studies have examined ED visits following elective foot and ankle procedures and open reduction and internal fixation (ORIF) for treatment of ankle fracture. 2 , 31 , 39 These studies report that postoperative ED visits are common, with 30-day incidences ranging from 7% to 22%. However, cohort sizes have been limited to less than 600 patients.…”
Section: Introductionmentioning
confidence: 99%
“…ED visits are reportedly common after elective foot and ankle surgery, with incidences ranging from 7% to 22%. [9][10][11] These studies, however, used single-institution cohorts with fewer than 600 patients evaluated within a 30-day postoperative period. Larger, nationwide studies are important for examining trends in postoperative ED utilization across the country.…”
mentioning
confidence: 99%